PENGARUH PENYULUHAN KEHUTANAN TERHADAP PERAN KEPEMIMPINAN INFORMAL DI LINGKUNGAN TAMAN NASIONAL GUNUNG CIREMAI PROVINSI JAWA BARAT - suyadi suyadi suyadi; sumardjo sumardjo; Zaim Uchrowi; Prabowo Tjitropranoto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Agroforestry farmers are generally less empowered and relatively poor. This is because of their dependance  on government programs. Informal leaders are one of the driving factors to improve farmers' empowerment. The power of informal leaders' influence is in line with the level of leadership in affecting the empowerment of farmers. Informal leadership will have more impacts on agroforestry farmers when it is supported by optimal forestry extension. This study aims to analyze the influence of forestry extension on the role of informal leadership to the community surrounding the national park. The research was conducted in Kuningan and Majalengka Districts, West Java Province,  which was held from July to October 2017. The method used was cluster random sampling technique with cluster location of agroforestry forest farmer group in the buffer zone of Gunung Ciremai National Park area. Data were collected by households survey on 310 agroforestry farmers. The results showed that informal leadership roles were low. This is due to the low support of forestry extension are indicated by forestry extension competency, activities, methods, materials and intensity of forestry extension. Factors of forestry extension agent's competencies and extension intensity have a major influence on the role of informal leadership.